Developing Android-Based E-Modules for Project-Based Learning in Basic Electrical - Annisa Tishana; Ahyanuardi Ahyanuardi; Dedy Irfan; Hansi Effendi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to develop a validated, useful, and efficient electronic module (e-module) on the Fundamentals of Electrical Engineering using a project-based methodology. The e-module is designed to enhance learners' understanding and improve their learning outcomes. The Research and Development (RD) approach, consisting of four stages—Define, Design, Develop, and Disseminate—was employed. Descriptive analysis was used to evaluate the validity of the e-module based on assessments by material and media specialists, as well as its practicality for teachers and students, and its impact on student learning. The results show that the e-module's validity was confirmed through descriptive analysis. Media experts rated it with a validation value of 0.88, and material experts gave a value of 0.92, both exceeding the threshold value of 0.61, indicating high validity. The practicality was measured by responses from teachers and students, with teachers giving an average score of 92.00% and students 96.79%, indicating the e-module is very practical. Effectiveness was assessed through the gain score of student learning outcomes, which was 0.65. This score falls into the medium category, as it is between 0.3 and 0.7. Therefore, the project-based Fundamentals of Electrical Engineering e-module has been shown to enhance learning outcomes effectively. In conclusion, the e-module has been validated for its content and media, proven practical by positive feedback from teachers and students, and demonstrated effective in improving learning outcomes, making it a valuable educational tool.